Patient safety in ambulatory care from the patient's perspective: a retrospective, representative telephone survey. Issue 2 (16th February 2020) - Geraedts, Max; Krause, Svenja; Schneider, Michael; Ortwein, Annette; Leinert, Johannes; de Cruppé, Werner
Abstract : Objectives: Data on patient safety problems (PSPs) in ambulatory care are scarce. The aim of the study was to record the frequency, type, severity and point of origin of PSPs in ambulatory care in Germany. Design: Retrospective cross-sectional study. Setting: Computer-assisted telephone interviews with randomly recruited citizens aged ≥40 years in Germany who were asked about their experiences with PSPs in ambulatory care. Participants: 10 037 citizens ≥40 years. Measures: A new questionnaire was developed to record patient experiences with PSPs in ambulatory care. The study reported here targets patient experiences in the last 12 months. The questionnaire focuses on PSPs in seven areas of medical treatment: anamnesis/diagnostic procedures; medication; vaccination, injection, infusion; aftercare; outpatient surgery; office administration; other areas. For each PSP reported, detailed questions were asked about the specialist group concerned, and, on the most serious harm, the severity of the harm and its consequences. The target parameters are presented as proportions with 95% CIs. Results: 1422 of the respondents (14%) reported 2589 PSPs. The areas most frequently affected by PSPs were anamnesis/diagnostic procedures (61%) and medication (15%). General practitioners accounted for 44% of PSPs, orthopaedists for 15% and internists for 10%. 75% of PSPs were associated with harm, especially unnecessarily prolonged pain or deterioration of health; 35% of PSPs led to permanent harm. 804 PSPs (32%) prompted patients to see another doctor for additional treatment; 255 PSPs (10%) required inpatient treatment. Conclusion: PSPs experienced by patients are widespread in ambulatory care in Germany. The study reveals in which areas of medical treatment efforts to prevent PSPs could make the greatest contribution to improving patient safety. It also demonstrates the valuable contribution of patient reports to the analysis of PSPs.